2020
DOI: 10.1098/rsos.200196
|View full text |Cite
|
Sign up to set email alerts
|

Stable body size of Alpine ungulates

Abstract: In many species, decreasing body size has been associated with increasing temperatures. Although climate-induced phenotypic shifts, and evolutionary impacts, can affect the structure and functioning of marine and terrestrial ecosystems through biological and metabolic rules, evidence for shrinking body size is often challenged by (i) relatively short intervals of observation, (ii) a limited number of individuals, and (iii) confinement to small and isolated populations. To overcome these issues and provide impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…Our study adds to the previous research on the decrease in body mass in adults (data from this population and from Italy [ 19 ]) and yearlings (data from Italy [ 22 ] and Austria [ 23 ]). A recent study, however, did not find any change in body mass or size in chamois and three other ungulate species in the eastern Swiss Alps between 1991 and 2013 [ 24 ]. Several possible explanations are mentioned by the authors, including less extreme local changes in temperatures and forage quality in their population compared with other regions of the Alps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study adds to the previous research on the decrease in body mass in adults (data from this population and from Italy [ 19 ]) and yearlings (data from Italy [ 22 ] and Austria [ 23 ]). A recent study, however, did not find any change in body mass or size in chamois and three other ungulate species in the eastern Swiss Alps between 1991 and 2013 [ 24 ]. Several possible explanations are mentioned by the authors, including less extreme local changes in temperatures and forage quality in their population compared with other regions of the Alps.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, most previous studies on the Alpine chamois have revealed a gradual shrinking in chamois body mass (e.g. [ 19 , 22 , 23 ], but see [ 24 ]). As observed previously by these studies, we expected a temporal decrease in the body mass of yearling chamois and a negative relationship with the temperature during spring–summer in the first two years of life (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example, as temperate climates warm, growing seasons are also extended. Thus, some studies indicate that the negative effect of increased temperature on size is counteracted by the longer period of time during which animals can feed and grow (Büntgen et al, 2020; Chown & Jaco Klok, 2003; Davison & Field, 2017). However, extended growing seasons do not explain all observed variation in size changes over the past decades because the majority of size declines have been reported from temperate regions, indicating that longer growing seasons cannot counteract the negative impacts of warming in all cases.…”
Section: Drivers Of Observed Body Size Changesmentioning
confidence: 99%